Facilitating sensorimotor integration via blocked practice underpins imitation learning of atypical biological kinematics in autism spectrum disorder. (August 2020) - Foster, Nathan C; Bennett, Simon J; Causer, Joe; Elliott, Digby; Bird, Geoffrey; Hayes, Spencer J
The reduced efficacy of voluntary imitation in autism is suggested to be underpinned by differences in sensorimotor processing. We examined whether the imitation of novel atypical biological kinematics by autistic adults is enhanced by imitating a model in a predictable blocked practice trial order. This practice structure is expected to facilitate trial-to-trial sensorimotor processing, integration and encoding of biological kinematics. The results showed that neurotypical participants were generally more effective at imitating the biological kinematics across all experimental phases. Importantly, and compared to a pre-test where imitation was performed in a randomised (unpredictable) trial order, the autistic participants learned to imitate the atypical kinematics more effectively following an acquisition phase of repeatedly imitating the same model during blocked practice. Data from the post-test showed that autistic participants remained effective at imitating the atypical biological kinematics when the models were subsequently presented in a randomised trial order. These findings show that the reduced efficacy of voluntary imitation in autism can be enhanced during learning by facilitating trial-to-trial processing and integration of sensorimotor information using blocked practice. Lay Abstract: Autistic people sometimes find it difficult to copy another person's movement accurately, especially if the movement is unfamiliar or novel (e.g. to use chop sticks). In this study, we found that autistic people were generally less accurate at copying a novel movement than non-autistic people. However, by making a small adjustment and asking people to copy this movement for a set number of attempts in a predictable manner, we showed that autistic people did successfully learn to copy a new movement. This is a very important finding for autistic people because rather than thinking they cannot copy new movements, all that needs to be considered is for parents/guardians, teachers and/or support workers to make a small adjustment so that learning occurs in a predictable manner for new skills to be successfully acquired through copying. The implications from this study are wide-ranging as copying (imitation) and motor learning are important developmental processes for autistic infants and children to acquire in order to interact within the world. Therefore, practising these behaviours in the most effective way can certainly help the developmental pathway.